2020
DOI: 10.1088/1674-1056/ab8896
|View full text |Cite
|
Sign up to set email alerts
|

Growth and aggregation of Cu nanocrystals on ionic liquid surfaces*

Abstract: We report a catalyst-free growth of Cu nanocrystals on ionic liquid surfaces by thermal evaporation method at room temperature. After deposition of Cu on ionic liquid surfaces, ramified Cu aggregates form. It is found that the aggregates are composed of both granules and nanocrystals with triangular or hexagonal appearances. The sizes of the nanocrystals are in the range of tens to hundreds of nanometers and increase with the nominal deposition thickness. The growth mechanism of the Cu aggregates and nanocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It is unanimously reported that a multi-step formation mechanism occurs when depositing metals on liquids [ 1 , 2 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 21 , 23 ,…”
Section: Introductionmentioning
confidence: 99%
“…Other groups followed this approach using different kinds of liquid substrate materials, such as silicone oils, ionic liquids and vegetable oils, to synthesize metal films and nanoparticles made of gold, silver, titanium, aluminum, iron, nickel and copper via sputtering and thermal evaporation processes [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. Besides, the growth of crystals from different aromatic hydrocarbons, zinc, copper and gold on silicone oil and ionic liquids by vapor phase deposition was studied [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. It is unanimously reported that a multi-step formation mechanism occurs when depositing metals on liquids [ 1 , 2 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 13 , 15 , 16 , 17 , 18 , 19 , 21 , 23 ,…”
Section: Introductionmentioning
confidence: 99%